INVENTARISASI SERANGGA POLINATOR DI LAHAN PERTANIAN SEMANGKA (Citrulus lanatus) KOTA PEKANBARU DAN PENGEMBANGANNYA UNTUK SUMBER BELAJAR PADA KONSEP KEANEKARAGAMAN HAYATI DI SMA - Okta Angriani Angriani; Mariani Natalina Linggasari Natalina Linggasari; Elya Febrita Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The research was conducted  to determine the types of insect pollinators on watermelon (Citrulus lanatus) agricultural land Pekanbaru City in February to June, 2014. Research results are used to teaching materials in the form of learning modules, insektarium media and interactive learning media. This research was carried out by two stage that is the field research stage and stage development of learning resources. Data retrieval technique using total sampling with threere search stations. Station I : located in the Naga Sakti Street, RT 02/RW 02, SimpangBaru Village, Tampan District, Pekanbaru. Station II : located in the Lintas Timur Street Kilometers 18, RT 05/RW 08, Kulim Village, Tenayan Raya District, Pekanbaru. Station III : located in the Ikan Parang Street, RT 03/RW 05, Muara Fajar Village, Rumbai District, Pekanbaru. Biological parameters observed are the type of insect pollinators and physical parameters include temperature, humidityand light intensity. The results showed that there are 13 species of insect pollinators belonging to 6 families and 3orders that the Order Hymenoptera, Order Lepidoptera and Order Diptera. Order Hymenoptera Family Apidae (2 species), Family Anthoporidae (1 species), Family Vespidae (1 species). Order Lepidoptera Famliy Nympalidae (5 species), Family Pieridae (3 species) and Order Diptera Family Syrphidae (1 species). Results of the study can beusedas a learning resourcein the form of learning modules, insectarium media and interactive learning media on biodiversity material class X High School. The average valueof learning resources developed ranged from 3.31 to 3.51with the validity criteria are very valid. The final stageof the research conducted limited testingof learning modules were tested in class X SMA N 8 Pekanbaru the number of students as many as 34 students. Based on the results of this research is that learning resources developed can already be implemented with the validity criteria are very valid. Key Word :Type Insect Pollinators, Plants Watermelon, Learning Resources